Arboles frutales en los campos agricolas de las fincas indigenas de Talamanca, Costa Rica - Burgos, A.=700 1 Armero, H.; Somarriba, E.
(Es, En)
ilus., 23 ref.
Keywords: MERCADEO; INVENTARIOS FORESTALES; FRUTALES; NEPHELIUM LAPPACEUM; THEOBROMA CACAO; ORGANISMOS INDIGENAS; VARIEDADES NATURALIZADAS; COSTA RICA; FRUTALES EXOTICOS